Impact of change orientation on cross cultural adaptability for effective execution of International Assignments - Dr.K. Jawahar Rani, Ms.K.P. Varalakshmi, (International Journal of Scientific Research and Management (IJSRM), 2017)
Successful assignment of expatriates is a very complex and challenging issue faced by multinationals. Expatriate failures are reported to be very high .This study attempts to find out how change orientation training given to the expatriates leads to cross cultural adaptability in their new International Assignments. It also helps us to know about how expatriates adapt themselves in new culture and environment at both organisational and personal level during their cross-cultural transitions. Majority of expatriates who has undergone cultural training were able to adapt themselves in the new host culture as they were prepared to accept the changes. Expatriates who has not undergone their cultural training finds it difficult to adapt themselves as they are not ready to change orientation and they face a lot of cultural shock.in the host country This study shows the association between change orientation and cross cultural adaptability and if more training is provided by the organisation for their expatriates they can become more change oriented and their adaptability also increases. The empirical study shows that there are differences between some of the demographic factors and cross-cultural adaptation.